2017
DOI: 10.14689/ejer.2017.67.11
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Contribute to Career Adaptability of High‐School Students

Abstract: In 2017 and 2018, engineering applications and design process were given weight to with the updates carried out in the Physical Sciences Lesson Curriculum in Turkey. For the STEM education which is at the center of this update to reach its target, it is highly important that students accurately learn what engineers do, what their work field is, the characteristics they should carry and understand the nature of engineering. The present study aims to identify the perception of engineers of 5th, 6th and 7th grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
2
15
0
5
Order By: Relevance
“…The CAAS, developed by Savickas and Porfeli (2012), was adapted for Turkish adolescents by Karacan-Özdemir (2016). A 24-item 5-point Likert-type scale (“1 = not strong,” “5 = strongest”), the CAAS consists of four subscales of concern (e.g., “Thinking about what my future will be like”), control (e.g., “Taking responsibility for my actions”), curiosity (e.g., “Observing different ways of doing things”) and confidence (e.g., “Overcoming obstacles”).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The CAAS, developed by Savickas and Porfeli (2012), was adapted for Turkish adolescents by Karacan-Özdemir (2016). A 24-item 5-point Likert-type scale (“1 = not strong,” “5 = strongest”), the CAAS consists of four subscales of concern (e.g., “Thinking about what my future will be like”), control (e.g., “Taking responsibility for my actions”), curiosity (e.g., “Observing different ways of doing things”) and confidence (e.g., “Overcoming obstacles”).…”
Section: Studymentioning
confidence: 99%
“…When the previous research on CCT is reviewed, it is observed that a significant number of studies have been conducted on career adaptability, which is one of the most essential concepts of the theory, and which refers to adaptability resources in the CCMA. For instance, career adaptability was found to be significantly related to self-esteem (Cai et al, 2015), career decidedness (Nota et al, 2012), career decision-making difficulties (Hirschi & Volero, 2015), hope and optimism (Buyukgoze-Kavas, 2016; Hirschi, 2014; Karacan-Özdemir & Yerin-Guneri, 2017; Santilli et al, 2014), and happiness (Patton et al, 2002). However, very few studies have attempted to fully evaluate the CCMA.…”
Section: Introductionmentioning
confidence: 99%
“…Kariyer uyum yeteneği ile ilgili ulusal alan yazınında yapılan çalışmalar incelendiğinde, son yıllarda bu konu ile ilgili araştırmalara ilginin arttığı ve çeşitli araştırmaların yapıldığı söylenebilir. Örneğin ölçek geliştirme (Erdoğmuş Zorver ve Korkut Owen, 2014), ölçek uyarlama (Büyükgöze Kavas, 2014;Işık vd., 2018;Kanten, 2012;Karacan Özdemir, 2016) çalışmalarının yanı sıra ilişkisel (Bölükbaşı, 2017;Karacan Özdemir, 2016;Kırdök ve Bölükbaşı, 2018;Mercan, 2016;Yiğit, 2018), nitel (Karacan Özdemir ve Ayaz, 2018) ve deneysel (Eryılmaz ve Kara, 2019;Kepir Savoly, 2017;Ömeroğlu, 2014;Turan, 2017) çalışmaların olduğu görülmektedir. Ulusal alan yazınında yapılan çalışmalar incelediğinde pozitif psikoloji bağlamında yapılan çalışmaların sınırlı olduğu söylenebilir.…”
Section: Introductionunclassified
“…Several studies have highlighted the importance of examining parent and adolescents’ perceptions simultaneously (Ginevra et al., 2015; Rogers et al., 2018), although researchers in Turkey have mostly examined adolescent perceptions of their parents’ support (Hamamcı et al., 2013; Karacan-Özdemir & Yerin Güneri, 2017; Öztemel, 2012). No studies have been conducted examining parental support and approaches towards their children’ career development.…”
Section: Introductionmentioning
confidence: 99%